Flat bed dryer adopted in at least four countries in Southeast Asia - CGIAR Research Program on Rice (2019)
The flat bed dryer originally developed by IRRI and improved by Nong Lam University of Vietnam targets farmers groups, processors and service providers and scaled by private manufacturers with assistance of public sector extension. Around 10,000 dryers were adopted in Vietnam, 1,000 in the Philippines, 1,700 in Cambodia and 400 in Myanmar.